The Syntactical Analysis of Compound Sentence Found in Crazy Rich Asians Novel - Putra, I Wayan Agus Adi; Putra , I Gusti Bagus Wahyu Nugraha; Maharani , Putu Devi (Journal of Language and Applied Linguistics, 2024)
Compound sentence is a sentence that has a couple or extra independent clause that connected by conjunction coordinator Fanboys, semicolon/coma, and conjunctive adverb. The center of this study is on compound sentence found in “Crazy Rich Asians” novel by Kevin Kwan. The aim of this study are follows: (1) to find out types of compound sentence in Crazy Rich Asians novel by Kevin Kwan. (2) to analyze the constituent structure of compound sentence found in Crazy Rich Asians novel by Kevin Kwan. Moreover, qualitative research method is used to analyze the data found in this study. In order to analyze the data, there are two theories are used. The first main theory is from Oshima and Hogue (1998) about type of sentence, and the second as supporting theory is from Brown and Miller (1991) about tree diagram structure. There are two ways of presenting the data in this study; formal and informal method. The formal method used in form of tree diagram and the informal method used words to explain the data descriptively. The result of the study shows type of compound sentence found in the novel. There are 38 data connected with coordinator, only 3 data connected by semicolon / coma, and the rest 2 following data connected with conjunctive adverb.